Appropriate transformation techniques to determine a modified standardized precipitation index for the ping river in Northern Thailand - Tanachot Chaito (2020)
© 2019, Thai Society of Higher Eduation Institutes on Environment. All Rights Reserved. The standardized precipitation index (SPI) is used to characterize precipitation when evaluating drought intensity over a range of timescales. From a statistical point of view, an appropriate standardization method depends on the limitations of the input data to make them effective as SPI values. For this reason, a modified SPI (TSPI) based on selecting an appropriate transformation for the distribution of the precipitation data is introduced in the present study. Firstly, a number of appropriate distributions were found to fit the seasonal rainfall data during the period of 1957-2014 for the Ping River in northern Thailand, and secondly, numerical analysis for various situations was carried out to compare the SPI and TSPI for each selected distribution. The results show that the TSPI performed well for all of the situations in the study. Finally, the TSPI was applied to identify rainfall characteristics in the data from three rain gauging stations on the Ping River in northern Thailand. The TSPI is recommended as an appropriate alternative to the SPI for drought analysis when limited to a small sample size such as the precipitation distribution of interest in this study.